Regulation by metformin of the hexose transport system in vascular endothelial and smooth muscle cells. - Sasson, S. (1996)
1. The effect of the biguanide metformin on hexose transport activity was studied in bovine cultured aortic endothelial (BEC) and smooth muscle cells (BSMC). 2. Metformin elevated the rate of hexose transport determined with 2-deoxyglucose (2DG) in a dose- and time-dependent manner in both cell types. Similar ED50 values (0.8-1.0 mM) were determined for the effect of metformin on 2DG uptake in both BEC and BSMC following 24 h exposure to increasing concentrations of metformin, with maximal stimulation at 2 mM. 3. In BEC, metformin increased the hexose transport rate 2-3 fold at all glucose concentrations tested (3.3-22.2 mM). In BSMC incubated with 22.2 mM glucose, metformin elevated the hexose transport approximately 2 fold. The drug was also effective at lower glucose levels, but did not exceed the maximal transport rate observed in glucose-deprived cells. 4. Similar results were obtained when the effect of metformin on hexose transport activity was assessed with the non-metabolizable hexose analogue, 3-O-methylglucose, suggesting that the drug affects primarily the rate of hexose transport rather than its subsequent phosphorylation. 5. The metformin-induced increase in hexose transport in BSMC treated for 24 h with the drug correlated with increased abundance of GLUT1 protein in the plasma membrane, as determined by Western blot analysis. 6. These data indicate that in addition to its known effects on hexose metabolism in insulin responsive tissues, metformin also affects the hexose transport system in vascular cells. This may contribute to its blood glucose lowering capacity in patients with Type 2, non-insulin-dependent diabetes mellitus.